Tax incentives as an instrument attracting investors to special economic zones - Jasiniak Magdalena; Jakub Koziński (e-Finanse: Financial Internet Quarterly, 2017)
Special Economic Zones have been operating in Poland since 1994 and are still growing. Tax incentives being offered in these Zones, as good infrastructure and administration support, are supposed to be attractions for newly established companies. The purpose of this article is to investigate whether tax incentives have an impact on the decision process of locating the investments in Special Economic Zones in Poland. The article presents a preliminary study, based on results of a questionnaire survey conducted among companies located in SEZ in Poland and presents subjective opinions of the investors about tax policy in SEZs. Results show that tax incentives are an important instrument attracting investors to Special Economic Zones. As the following analysis presents, tax reliefs seem to be an important investment incentive, however, the importance of income taxes is greater than the local costs to doing business. There are also some differences in evaluating tax support depending on a company's size and the level of support in a particular region.
Keywords: H23; H25; H71; F21; F23; 330; Special Economic Zones; tax incentives; regional development; investment attractiveness